Strategy for Introducing Basic Mathematics Based on Jumping Geometry Game for Early Childhood - Kusumastuti, Narendradewi; Ngaisah, Nur Cahyati (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Memorization, writing and counting activities become something that is considered very difficult if the concept has not been mastered. Mathematical skills in understanding basic mathematical concepts can be trained first in recognizing geometric shapes before recognizing number symbols. This can be done through geometry lombat games that are played directly by the child. The purpose of this study is that educators can use innovative strategies in the introduction of basic math for children, which can be done through games that are fun and meaningful for children. The research method used descriptive qualitative with 8 subjects conducted at Pertiwi Nglebak Ngawi Kindergarten. The research technique used observation, interview and documentation techniques. And then the results are analyzed until they reach a conclusion. The findings in this study are that the strategy of introducing basic mathematics based on geometry jumping games is very suitable to be implemented for children aged 4-5 years. Geometry jumping games can introduce children to geometric shapes such as triangles, circles, squares and rectangles. In addition, children can remember the names of shapes and characteristics of geometric shapes easily and fun.